Low Power Standard Cell Library Design For Application Specific Integrated Circuit - Jambek, Asral Bahari (2002)
With the expansion of portable and wireless electronics product in the current market demand, the focus of designing VLSI system has shifted from high speed to low power domain. This requires chip designers to minimize power consumption at all design level such as system, algorithm, architecture, circuit and technology. The objective of this work is to develop low power CMOS standard cell library to be used in application specific integrated circuit (ASIC) design flow. The design methodology focuses on all aspect of circuit design: transistor size, logic style, layout style, cell topology, and circuit design for minimum power consumption. The standard cell library is targeted for general-purpose application, especially in microprocessor design. For rapid design implementation, the library is designed to be used together with the commercial logic synthesis and automatic cell placement and routing tools. Results show that the microprocessor targeted to the low power library gives 44% power saving compared to the conventional library, with both designs operate at the same clock frequency of 50MHz.